HAKEKAT PERKAWINAN MENURUT UNDANG-UNDANG PERKAWINAN, HUKUM ISLAM DAN HUKUM ADAT - Santoso Santoso (Program Studi Hukum Keluarga Islam, 2016)
Indonesia has constructed marriage law based on Pancasila despite the variety of marriage practice in the society. The Law No 7 of 1974 on Marriage does not regulate the practice of marriage based on local culture.According to the Law, a marriage is valid as long as conducted in accordance with one‟s religion or belief system. Furthermore to be accepted as legal, a marriage should be registered in the Office of Civil Registration or Office of Religious Affairs.